The Privacy Mismatch: Evolved Intuitions in a Digital World. (April 2021) - Shariff, Azim; Green, Joe; Jettinghoff, William
Although people report grave concern over their data privacy, they take little care to protect it. We suggest that this privacy paradox can be understood in part as the consequence of an evolutionary mismatch: Privacy intuitions evolved in an environment that was radically different from the one found online. This evolved privacy psychology leaves people disconnected from the consequence of online privacy threats.